Evidence based diagnosis and management of chronic subdural hematoma: A review of the literature. (April 2018) - Mehta, Vikram; Harward, Stephen C.; Sankey, Eric W.; Nayar, Gautam; Codd, Patrick J.
Highlights: Chronic subdural hematomas are fluid pockets encapsulated by dural border cells. Imaging shows crescentic layering of fluid on non-contrast CT. Operative intervention if compression on imaging or patients is symptomatic. Craniostomy (burr hole/twist drill) and craniotomy are equally effective surgeries. Post-operatively, subdural drains reduce recurrence and SCDs reduce DVTs. Abstract: Chronic subdural hematomas are encapsulated blood collections within the dural border cells with characteristic outer "neomembranes". Affected patients are more often male and typically above the age of 70. Imaging shows crescentic layering of fluid in the subdural space on a non-contrast computed tomography (CT) scan, best appreciated on sagittal or coronal reformats. Initial medical management involves reversing anticoagulant/antiplatelet therapies, and often initiation of anti-epileptic drugs (AEDs). Operative interventions, such as twist-drill craniostomy (TDC), burr-hole craniostomy (BHC), and craniotomy are indicated if imaging implies compression (maximum fluid collection thickness >1 cm) or the patient is symptomatic. The effectiveness of various surgical techniques remains poorly characterized, with sparse level 1 evidence, variable outcome measures, and various surgical techniques. Postoperatively, subdural drains can decrease recurrence and sequential compression devices can decrease embolic complications, while measures such as early mobilization and re-initiation of anticoagulation need further study. Non-operative management, including steroid therapy, etizolam, tranexamic acid, and angiotensin converting enzyme inhibitors (ACEI) also remain poorly studied. Recurrent hemorrhages are a major complication affecting around 10–20% of patients, and therefore close follow-up is essential.